A Case Study on Key Account Management at Printo - Palanivelu, Anand Raj (2011)
Key Account Management (KAM) is considered to be the active contributor to the realization of the unique selling position of the firm and therefore it creates a competitive advantage that increases the performance of the firm, which leads to the shareholder holder value – the ultimate aim of doing business. As Cheverton describes KAM as is about managing the future of the business and Hellman describes it as a specific program that overcomes the barriers in business growth. This management research project focuses on Key Account Management in the real business environment. KAM process in Printo Document Services Private Limited was studied and reviewed against various academic literatures which focused on business-to-business segments. There were few emerging themes that were analyzed in the business context and its impact on the business, especially balanced customer portfolio matrix, relationship management, value creation and delivery process and organizational orientation towards value creation. The correlation between these emerging themes and the business objectives was done throughout the research. The outcome of the research was that balancing the customer portfolio is as important as adding the customers in the Key Account quadrant. Relationships and managing the relationship with the customer is important in the Business-to-Business environment. Factors like customer satisfaction, customer loyalty, sales-person’s involvement and constant review of the relationship with the customers have been found critical in relationship management. Customers do business with a vendor only if they see value addition to their business and hence, value creation is the key for the success of any product or service. Delivering value is as critical and important as creating one and it was found that organizational orientation towards customer focus and value creation to customers ensures customer satisfaction and loyalty. This research project report concludes with the recommendations to the business considering the above mentioned themes in building their sales strategy to the B2B segment, which was the prime objective of this internship project.